2009
DOI: 10.1007/s00299-009-0758-3
|View full text |Cite
|
Sign up to set email alerts
|

Production of recombinant single chain antibodies (scFv) in vegetatively reproductive Kalanchoe pinnata by in planta transformation

Abstract: We developed an asexual reproductive plant, Kalanchoe pinnata, as a new bioreactor for plant-based molecular farming using a newly developed transformation method. Leaf crenate margins were pin-pricked to infect the plant with the Agrobacterium strain LBA4404 and vacuum infiltration was also applied to introduce the target gene into the plants. Subsequently, the young mother leaf produced new clones at the leaf crenate margins without the need for time-and labor-consuming tissue culture procedures. The average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…RNA was quantified by UV (230/260 nm), precipitated, resuspended in DEPC‐treated water at a concentration of 5 μg/μL and stored at −85 °C. cDNA was synthesized from 5 μg of RNA with Moloney Marine Leukemia Virus (MMLV) reverse transcriptase (Promega, Madison, WI, USA) using 200 ng oligo‐dT primers at 50 °C for 60 min (Jung et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…RNA was quantified by UV (230/260 nm), precipitated, resuspended in DEPC‐treated water at a concentration of 5 μg/μL and stored at −85 °C. cDNA was synthesized from 5 μg of RNA with Moloney Marine Leukemia Virus (MMLV) reverse transcriptase (Promega, Madison, WI, USA) using 200 ng oligo‐dT primers at 50 °C for 60 min (Jung et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this antibody is superior to accumulate at low levels and to induce no harmful effects on plant development in spite of its sequence-independent activity (Lee et al, 2013a). It has been reported that expression of 3D8 scFv confers resistance to DNA or RNA viruses in tobaccos and Chinese cabbages (Brassica rapa) (Lee et al, 2013a;Lee et al, 2013b;Jung et al, 2009). When CSVd was inoculated into transgenic chrysanthemums expressing the conventional 3D8 scFv or codon-optimized for chrysanthemum, no disease symptoms were observed in either case, and all transgenic lines showed no disease symptoms.…”
Section: -3-1-2 Nucleic Acid Antibodymentioning
confidence: 99%
“…sp.) suckers [153], gemmae of umbrella liverwort (Marchantia polymorphya) [154], leaf notches of cathedral bells (Kalanchoe pinnata) [155], sugarcane (Saccharum spp.) setts [156], and bulbs of the Notocactus scopa and Hylocereus trigonus cacti [157].…”
Section: Propagule Transformationmentioning
confidence: 99%